2008
DOI: 10.1007/s10165-008-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with plasma exchange in adult-onset Still’s disease with hyper-IL-18-naemia and hyperallergic state

Abstract: Adult-onset Still's disease (AOSD) is a rheumatoid disorder characterized by high fever, polyarthritis, leukocytosis, hyperferritinaemia, and mild liver involvement. We describe the case of a patient with AOSD with severe liver dysfunction. His serum levels of interleukin-10 and 18 showed a similar trend to his disease activity. Drug lymphocyte stimulation tests were positive for three drugs in the patient. Hypercytokinaemia was controlled by plasma exchange therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…It has a marked corticosteroid-sparing effect and a good tolerance profile [ 48 , 49 ]. Plasma exchange and intravenous immunoglobulins are other treatment options in refractory AOSD patients [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a marked corticosteroid-sparing effect and a good tolerance profile [ 48 , 49 ]. Plasma exchange and intravenous immunoglobulins are other treatment options in refractory AOSD patients [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma exchange is an extracorporeal blood purification technique designed to remove various toxic and inflammatory mediators and to replenish essential compounds via the replacement plasma, which is known also to decrease ferritin levels [16]. It is a successful therapy in all four clinical conditions discussed, although in the case of the AOSD, there are only anecdotal cases [59,73-75,77,78,81,85-88]. …”
Section: Clinical and Laboratory Features In Mas Aosd Caps And Septmentioning
confidence: 99%
“…Plasma exchange has been reported to be effective for AOSD-associated MAS (35)(36)(37). Ito et al demonstrated the prompt improvement of hypercytokinemia due to IL-6 and IL-18 using plasma exchange and a high-dose corticosteroid (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al demonstrated the prompt improvement of hypercytokinemia due to IL-6 and IL-18 using plasma exchange and a high-dose corticosteroid (37). The HLH 2004 protocol recommends the use of CyA concomitantly from an early stage in the cases of AOSD-associated MAS (38).…”
Section: Discussionmentioning
confidence: 99%